SEL LEMAK DAN PERANANNYA DALAM PENYAKIT - Ika Fidianingsih (Universitas Islam Indonesia, 2007)
ABSTRACTIt is well know that adipose tissue mass increase greatly in obesity. In Indonesia obesityprevalence tends to increase. It raised the risk of morbidity and total cost attributable to obesityrelated disease. The adipose tissue is energy storage, fatty acids being released when fuel isrequired. It is now adipose tissue expresses and secretes factors with impotant endicrine functions.These factor include adiponectin, adipsin, leptin, protein of the renin-angiotensin system,plasminogen activator-1, other cytokines and resistin. A better understanding of the endocrinefunction of adipose tissue will give evidence of links between increased productios of someadipocyte factors and the metabolic and cardiovascular complications of obesity.Key words: adipose tissue, obesity, endocrine organ